The effect of source suspended sediment concentration on the sediment dynamics of a macrotidal creek and salt marsh. (15th September 2017) - Poirier, Emma; van Proosdij, Danika; Milligan, Timothy G.
Abstract: Seasonal variability in the sediment dynamics of a Bay of Fundy tidal creek and salt marsh system was analyzed to better understand the ecomorphodynamics of a high suspended sediment concentration intertidal habitat. Data were collected over 62 tides for velocity, suspended sediment concentration, deposition, and grain size at four stations from the creek thalweg to the marsh surface. Five topographic surveys were also conducted throughout the 14-month study. Deposition rates per tide varied spatially from 56.4 g m -2 at the creek thalweg to 15.3 g m -2 at the marsh surface. Seasonal variations in deposition in the creek and marsh surface were from 38.0 g m -2 to 97.7 g m -2 and from 12.2 g m -2 to 19.6 g m -2 respectively. Deposition and erosion were greatest in late fall and winter. This seasonal change, led by higher suspended sediment concentrations, was observed in the creek and at the marsh bank but notably absent from the marsh edge and marsh surface. Sediments were predominantly deposited in floc form (76–83%). Because of high floc content, higher suspended sediment concentrations led to more rapid loss of sediment from suspension. With increasing sediment concentration, deposition increased in the tidal creek and at the marsh bank but not at the marsh edge or marsh surface. This suggests that in highly flocculated environments the water column clears fast enough that very little sediment remains in suspension when the water reaches the marsh and that the sediment concentration during marsh inundation is independent of the initial concentration in the creek. Highlights: In Upper Bay of Fundy, marsh surface sediment deposition independent of creek SSC. Sediment concentration on the flood tide is highest during the winter. Flocculation and settling of the flooding suspension increases with concentration. Sediment concentration in the water flooding the marsh does not vary seasonally.